Compendium of indicators for food system assessments - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Published in 2020 and available online. Several institutions have requested a copy and showed interest. Authors are aware of some external partners that are starting to use the compendium in their work. There will be more potential applications in the Healthy Food Africa project, to be reported in 2021.